'I Can't Afford to Buy All the Books I Read': What Public Libraries Offer Leisure Readers. Issue 2 (3rd April 2022) - Hider, Philip
ABSTRACT: A questionnaire survey was administered to working-age adults who read for leisure, with a focus on how public libraries supported this reading, in July 2021. The sample was drawn from student cohorts of an Australian university. A total of 187 respondents, with a median age of 35–44, obtained leisure reading materials from public libraries. Many of these respondents also sourced materials from elsewhere; these materials tended to be similar to the library materials, but otherwise were more likely to be non-fiction and online. Public library materials were used not only because they were free, but also because they were readily accessible, catered for different tastes and interests, and provided readers who favoured print copies with an environmentally sustainable option; libraries also assisted with reading choices. Respondents derived a range of interrelated benefits from their leisure reading: as well as pleasurable, it could be both educational and relaxing; it could also provide new perspectives and insights, as well as improve literacy. Leisure reading played an extremely important, even vital, role in many respondents' lives, and, given that for many of the readers purchasing all their materials was not an affordable option, the public library is a key facilitator of this activity.